Arts, Artworks and Manuscripts in Sicily between the 12th and 13th Centuries: Interactions and Interchanges at the Mediterranean Crossroads - Giulia Arcidiacono (Arts, 2023)
This research explores the figurative culture that flourished in Sicily during the 12th and 13th centuries, focusing on the interplay between artifacts of different types, materials, techniques and uses. Paintings, sculptures and objects that share a common visual language are analyzed with the aim of highlighting recurring motifs, mutual influences and related sources. The main focus is on the decorative apparatus of the Sacramentary Ms. 52 (Madrid, Biblioteca Nacional de España), one of the most famous illuminated manuscripts from Sicily. The date, origin and patronage of this luxurious liturgical book have been the subject of intense scholarly debate. In order to shed light on these controversial issues, this study re-examines the various hypotheses considered by scholars, taking into account the historical events that affected Sicily from the end of the Norman to the beginning of the Swabian era. This analysis also shows how the decoration of the manuscript fits into the wider dynamics of cultural exchange that characterized Sicily and the Mediterranean during this transitional period.